Information literacy as an integral element of the information culture of future teachers - Akimova О.; Kupina, O. (Problems of Engineer-Pedagogical Education, 2021)
The article characterizes the concept of "culture" as a polysemantic category, based on numerous theoretical and methodological approaches to understanding the content and diversity of fields of knowledge, according to which the concept is analyzed. It was found that the term "information culture" was first used in the scientific literature by G. Vorobyov, but his own interpretation of information culture was not formulated at that time. The authors also note that in the information educational environment, "culture" can be seen as information memory and as an evolutionary step towards the accumulation of unique individual experience and its transfer to the individual in the form of tools, means, signs and texts, various types of data independent of the individual. It is noted that the study of the content of information culture can be carried out in two main aspects: sociological and technological. The socio-cultural approach determines the level of formation of information culture on the basis of information communication – forms and methods of information communication without personal presence in the mode of communication. The formation of information culture via the technological approach outlines the need for a high level of knowledge about ways to find, store, create, disseminate and present any information, as well as the ability to solve pedagogical problems with digital tools and gadgets working with information, serving as a basis for information literacy. It is established that information literacy is an indicator of both information and professional culture of the future teacher. The system of knowledge, skills and abilities is given, which, according to the authors, are the basis of information literacy of the future specialist. According to the DigComp digital competency framework, the following general competencies are listed: information literacy, communication and collaboration, digital content creation, security, problem solving. In the content of the concept of "information culture" the elements of information literacy as a constituent element are singled out. The components of information literacy that should be formed in future teachers have been identified. The article presents the selected criteria for the formation of information culture of future teachers.